Koinon and koinônia: A Particular Case of Participation in John Philoponus - Granata, Daniele (Peitho. Examina Antiqua, 2018)
The aim of this study is to discuss an original philosophical contribution made by Philoponus, who in In Cat. 18, 14–22 equates koinon in its most peculiar meaning with the concept of koinônia understood as a particular case of Platonic methexis. First, the paper analyzes the passages where the Neoplatonic commentators of the Categories distinguish four distinct meanings of the Aristotelian concept of koinon. Subsequently, this article emphasizes the differences between Philoponus’ hermeneutical suggestions and those of the other commentators. Philoponus clarifies that while every koinon is methekton, Aristotle’s koinon is characterized by the fact that the participation is ex isou and kata meros. Thus, koinônia, according to Philoponus, is a particular case of methexis, where everyone participating in something participates in it equally and singly. The example cited by Philoponus to explain Aristotle’s koinon is that of men participating equally and singly in human nature. The study concludes with a discussion of the relationship among the concepts of koinon, koinônia and methexis.